B cells from anti-thyroid antibody positive, infertile women show hyper-reactivity to BCR stimulation - Serény-Litvai, Timea; Bajnok, Anna; Temesfoi, Viktoria; Nörenberg, Jasper; Pham-Dobor, Greta; Kaposi, Ambrus; Varnagy, Akos; Kovacs, Kalman; Pentek, Sandor; Koszegi, Tamas; Mezosi, Emese; Berki, Timea (Frontiers in Immunology, 2022)
Anti-thyroid antibody (ATA) positivity affects 1 out of 9 women in childbearing age and presents a significant risk for infertility. Emerging evidence indicates that alterations in the B cell receptor induced calcium (Ca2+) signaling could be key in the development of autoimmunity. We aimed to investigate the Ca2+ flux response of B lymphocyte subsets to BCR stimulation in Hashimoto’s thyroiditis and related infertility. We collected peripheral blood samples from ATA+, infertile, euthyroid patients (1), hypothyroid, ATA+ patients before (2) and after levothyroxine treatment (3), and age-matched healthy controls (4). All B cell subsets of ATA+, infertile, euthyroid patients showed elevated basal Ca2+ level and hyper-responsivity to BCR ligation compared to the other groups, which could reflect altered systemic immune function. The Ca2+ flux of hypothyroid patients was similar to healthy controls. The levothyroxine-treated patients had decreased prevalence of CD25+ B cells and lower basal Ca2+ level compared to pre-treatment. Our results support the role of altered Ca2+ flux of B cells in the early phase of thyroid autoimmunity and infertility.